NUMERICAL STUDY OF MAGNETOHYDRODYNAMIC MIXED CONVECTIVE FLOW IN A LID -DRIVEN ENCLOSURE FILLED WITH NANOFLUID SATURATED POROUS MEDIUM WITH CENTER HEATER - Mahalakshmi, Thangavelu; Nithyadevi, Nagarajan; Öztop, Hakan Fehmi (Vinca Inst Nuclear Sci, 2019)
This present numerical study explores the MHD mixed convectiveflow and heat transfer analysis in a square porous enclosure filled with nanofluid having center thin heater. The left and right walls of the enclosure are maintained at temperature T. The bottom wall is considered with a constant heat source whereas the remaining part of bottom wall and top wall are kept adiabatic. The finite volume method based on SIMPLE algorithm is used to solve the governing equations in order to investigate the effect of heater length, Hartmann, Richardson, and Darcy numbers on the fluid -flow and heat transfer characteristics inside the enclosure. A set of graphical results are presented in terms of streamlines, isotherms, mid height velocity profiles and average Nusselt numbers. The results reveal that heat transfer rate increases as heater length increases for increasing Darcy and Richardson numbers. Among the two positions of heaters, larger enhancement of heat transfer is obtained for horizontal heater of maximum length. It is observed that, Hartmann number is a good control parameter for heat transfer in fluid -flow through porous medium in enclosure. Moreover, Ag-water nanofluid has greater merit to be used for heat transfer enhancement. This problem may be occurred in designing cooling system for electronic equipment to maximize the efficiency with active and secured operational conditions.
Keywords: mixed convection; magnetic field; square enclosure; porous medium; nanofluid-flow; center heater.